BALL KINEMATICS IN FINE POLISHING BETWEEN MISALIGNED DISKS IN CONIC OPENINGS - K. G. Shchetnikovich; M. G. Kiselev (Наука и техника)
The paper considers ball kinematics in polishing between misaligned disks rotating with equal angular velocity; one of these disks has conic openings. Analytical dependences have been obtained for calculation of an angular velocity and ball sliding speed in the conic opening. It has been revealed that at a constant contact of a ball with elastic coating of a flat disk and absence of vibrations in the technological system an instantaneous axis of ball rotation does not change its position in the moving ball. It has been ascertained that when a ball is in contact with a flat disk having elastic coating with grooves changes in the position of ball rotation instantaneous axis have a regular character and do not depend on vibrations in the technological system.